O014/#415 Phase II trial of pembrolizumab and epacadostat in recurrent clear cell carcinoma of the ovary: an NRG oncology study. (4th December 2022) - Gien, Lilian; Enserro, Danielle; Block, Matthew; Waggoner, Steven; Duska, Linda; Hendrickson, Andrea Wahner; Thaker, Premal; Backes, Floor; Bottsford-Miller, Justin; Muller, Carolyn; Disilvestro, Paul; Covens, Allan; et al.
Abstract : Objectives: Early reports of PD-1 inhibition in ovarian clear cell carcinomas demonstrate promising durable response. We evaluated the combination of pembrolizumab and IDO-1 inhibitor epacadostat in patients with recurrent ovarian clear cell carcinomas. Methods: This single arm, two-stage, phase 2 trial included those with measurable disease and 1–3 prior regimens. Patients received intravenous pembrolizumab 200 mg every 3 weeks and epacadostat orally 100 mg twice a day. Primary endpoint was overall response rate (ORR), with secondary endpoints of toxicity, progression-free survival (PFS) and overall survival (OS). Results: Between September 28, 2018 and April 10, 2019, 14 patients accrued at first stage. Rate of accrual was 2.3 patients per month, higher than estimated. Median age was 65 (44–89), 10 (71.4%) had ≥ 2 prior regimens. ORR was 21% (95% CI 5–51%) within 7 months of study entry with 3 partial responses, 4 had stable disease for disease control rate of 50%. Median PFS was 4.8 months (95% CI: 1.9–9.6), OS 18.9 months (95% CI: 1.9-NR). Most common grade ≥ 3 adverse events reported were electrolyte changes and bowel obstruction. In July 2019, the study reached the pre-specified criteria to re-open to second stage, however after holding for amendment, the study closed prematurely in February 2021 due to insufficient drug supply. Conclusions: Combination of pembrolizumab and epacadostat demonstrated an ORR of 21% in this small cohort of recurrent ovarian clear cell carcinomas. The rapid rate of accrual highlights the enthusiasm and need for therapeutic studies in patients with ovarian clear cell carcinomas.